Alkaline Salts to Counteract Bone Resorption and Protein Wasting Induced by High Salt Intake: Results of a Randomized Controlled Trial - Bühlmeier, Judith; Frings-Meuthen, Petra; Remer, Thomas; Maser-Gluth, Christiane; Stehle, Peter; Biolo, Gianni; Heer, Martina (The Journal of Clinical Endocrinology & Metabolism)
Keywords: Biochemistry (medical); Clinical Biochemistry; Endocrinology; Biochemistry; Endocrinology; Diabetes and Metabolism

Figurationen der Krise: Literarische Feuilletons der 20er und frühen 30er Jahre. Forschungsbericht - Öhlschläger, Claudia; Kernmayer, Hildegard (Zeitschrift für Germanistik, Neue Folge, XXII, H. 3/2012)

Das punctum der Moderne. Fotobücher und feuilletonistische Städtebilder der 1920er und frühen 1930er Jahre - Öhlschläger, Claudia; Kernmayer, Hildegard (Zeitschrift für Germanistik Heft 3/2012)

Lexikalische Strategietherapie für Vorschulkinder mit dem Wortschatzsammler - Ulrich, Tanja; Schneggenburger, K (Sprachförderung und Sprachtherapie in Schule und Praxis)

Effects of the Strategy Therapy "Lexicon Pirate" on Lexical Deficits in Preschool age: a Randomized Controlled Trial. - Motsch, H.J; Ulrich, Tanja (Child Language Teaching and Therapy)

„Wortschatzsammler und Wortschatzfinder“- Effektivität neuerTherapieformate bei lexikalischen Störungen im Vorschulalter - Motsch, H.J; Ulrich, T (Die Sprachheilarbeit)

Geschichte und Präsenz. Überlegungen zum gegenwärtigen ‚Ort‘ historischen Erzählens am Beispiel von Javier Cercas’ Anatomie eines Augenblicks - Schlieper, Hendrik (Literatur und Theorie seit der Postmoderneu)

The Female Threshold. On Paratext and Gender in Lafayette’s La Princesse de Montpensier - Schlieper, Hendrik; Steinbrügge, Lieselotte (Papers on French Seventeenth Century Literature 76)

Diskrepante Väterfiguren: Haus, Familie und Liebe in Molières „École des femmes“ - Steigerwald, Jörn (Romanistische Zeitschrift für Literaturgeschichte)

Realismus nach den europäischen Avantgarden. Ästhetik, Poetologie und Kognition in Literatur und Film der Nachkriegszeit

Suchbewegungen im Raum des Humanitären. Topographien der Bewohnbarkeit im Nachkriegsrealismus von Heinrich Böll und Vasco Pratolini - Öhlschläger, Claudia; Römhild, Friederike (Realismus nach den europäischen Avantgarden. Ästhetik, Poetologie und Kognition in Literatur und Film der Nachkriegszeit)

Chronik eines Verlusts. Rekonfigurationen der Heiligen Familie in Michelangelo Antonionis ́Il Grido ́ (1957) - Öhlschläger, Claudia (Antonioni revisited)

Abstraktion im Licht der Faszination. Wilhelm Worringer am Ort des Primitivismus - Öhlschläger, Claudia (Literarischer Primitivismus)

Wiederabdruck von: "Medialität und Poetik des trompe l ́œil. W.G. Sebald und Jan Peter Tripp“ - Öhlschläger, Claudia (W.G. Sebald. Neue Wege der Forschung)

„Meraviglioso Adone“: Das Wunderbare als Lizenz episch-didaktischer Dichtung bei Giovan Battista Marino - Steigerwald, Jörn (Valeska Erosionen der Rhetorik? Ambiguitäts- und Umsemantisierungsstrategien in den Künsten der Frühen Neuzeit)

La galanterie des dieux antiques: Chapelain critique de l’“Adone“ du cavalier Marin - Steigerwald, Jörn (Littératures classiques 77)

Affekt-Erzählungen: Die galanten Novellen Scudérys und Villedieus - Steigerwald, Jörn (Galanterie als Verhaltenskonzept in der Literatur der Frühen Neuzeit)

Schöne neue Menschen: Michel Houellebecqs „Les particules élémentaires“ - Steigerwald, Jörn (Menschen machen. Die hellen und die dunklen Seiten humanwissenschaftlicher Optimierungsprogramme)

Die Grenzen der Höflichkeit : Molières „Le Misanthrope“ - Steigerwald, Jörn (Rhetorik. Ein internationales Jahrbuch)

Positionierung. Zur Entwicklung des Gebrauchs modalisierender Prozeduren in argumentativen Texten von Schülern und Studenten - Rezat, Sara; Gätje, Olaf; Steinhoff, Torsten (Textroutinen. Theorie, Erwerb und didaktisch-mediale Modellierung)

Mittendrin statt nur dabei: Inklusion in Krippe und Kindergarten - Albers, Timm

Zuwanderungsgeschichte(n) – Überlegungen zur Relevanz biografischen, interkulturellen Schreibens im Deutschunterricht - Zierau, Cornelia (Alman Dili ve Edebiyatı Dergisi. Studien zur deutschen Sprache und Literatur XXVII 1/2012)

Mehrsprachigkeit als Thema des Literaturunterrichts. Erzählungen von Emine Sevgi Özdamar und Yoko Tawada - Zierau, Cornelia (Literatur im Unterricht: Texte der Gegenwartsliteratur für die Schule (LiU) 13/2012: Heft 3)

Extending UML for Electronic Systems Design: A Code Generation Perspective - Vanderperren, Yves; Müller, Wolfgang; He, Da; Mischkalla, Fabian; Dahaene, Wim (Design Technology for Heterogeneous Embedded Systems)
The Unified Modeling Language (UML) is now widely accepted by the software community. More recently, UML has attracted attention as a unification language for systems description combining both hardware and software components. First, it has been recognized that electronic systems design can no longer be seen as an isolated hardware design activity. In addition, recent advances in tools supporting high level hardware synthesis from electronic system level languages, which are predominantly based on C/C++, open new perspectives for automatic code generation from UML models and opportunities to enhance the link between a high level specification and a concrete hardware/software implementation. Finally, UML has become a general purpose language which can be customized for specific purposes, such as the modelization of electronic systems. This chapter presents recent advances of the UML language applied to System-on-Chip (SoC) and hardware-related embedded systems design. In particular, several examples of specific UML customizations (UML profiles) relevant for SoC design are summarized. Various approaches associating UML with existing hardware/software design languages are presented. The question of tool support and association with well-known simulation environments, such as MATLAB/Simulink, is addressed as well. A concrete example of a UML profile for hardware/software co-modeling and code generation for hardware/software co-simulation is presented in more details for illustration purposes.

Die Geschichte meiner ‚Stoffe’. Literarische Umsetzung Erkenntnistheoretischer Fragen in Friedrich Dürrenmatts autobiographischem Projekt 'Stoffe I-IX' - Famula, Marta (Vielheit und Einheit der Germanistik weltweit (= Publikationen der Internationalen Vereinigung für Germanistik 8))

Förderschwerpunkt Lernen – wohin? - Rauh, B; Laubenstein, Désirée; Anken, L.; Auer, H.-L.

Simulation and Experimental Analysis of Mixed Lubrication of K Type Worm Gear Drives - Magyar, Balázs; Sauer, B; Horák, P

Kontaktmodellierung von technisch rauen Oberflächen - Magyar, Balázs; Sauer, B

Eine Schule für alle oder eine Schule für jeden – Gedankenfragmente zu diskursiven Praktiken im Rahmen aktueller Inklusionsdiskussionen - Laubenstein, Désirée (Sonderpädagogik und Inklusion)

Genderforschung im Feld der beruflichen Orientierung und Qualifikation von Menschen mit Benachteiligungen/Behinderungen - Laubenstein, Désirée; Heger, M. (In: Heilpädagogische Forschung, Band 38, Heft 2)

Dran bleiben. Benachteiligungen von jungen Frauen im beruflichen System finden immer noch zu wenig Beachtung - Heger, M.; Laubenstein, Désirée (In: Impulse, Nr. 60)

Tribological Investigation of K Type Worm Gear Drives - Magyar, Balázs; Sauer, B; Horák, P (Acta Polytechnica Hungarica)

Tribo-dynamische Untersuchungen von Zylinderschneckengetrieben - Magyar, Balázs

Academic procrastination: The perspective of university counsellors - Patrzek, Justine; Grunschel, Carola; Fries, Stefan (International Journal for the Advancement of Counselling)

Transient and Steady-State Shear Banding in a Lamellar Phase as Studied by Rheo-NMR - Medronho, Bruno; Olsson, Ulf; Schmidt, Claudia; Galvosas, Petrik (Zeitschrift für Physikalische Chemie)
Abstract Flow fields and shear-induced structures in the lamellar (L α ) phase of the system triethylene glycol mono n -decyl ether (C 10 E 3 )/water were investigated by NMR velocimetry, diffusometry, and 2 H NMR spectroscopy. The transformation from multilamellar vesicles (MLVs) to aligned planar lamellae is accompanied by a transient gradient shear banding. A high-shear-rate band of aligned lamellae forms next to the moving inner wall of the cylindrical Couette shear cell while a low-shear-rate band of the initial MLV structure remains close to the outer stationary wall. The band of layers grows at the expense of the band of MLVs until the transformation is completed. This process scales with the applied strain. Wall slip is a characteristic of the MLV state, while aligned layers show no deviation from Newtonian flow. The homogeneous nature of the opposite transformation from well aligned layers to MLVs via an intermediate structure resembling undulated multilamellar cylinders is confirmed. The strain dependence of this transformation appears to be independent of temperature. The shear diagram, which represents the shear-induced structures as a function of temperature and shear rate, contains a transition region between stable layers and stable MLVs. The steady-state structures in the transition region show a continuous change from layer-like at high temperature to MLV-like at lower temperature. These structures are homogeneous on a length scale above a few micrometers.
Keywords: Physical and Theoretical Chemistry

Novel Self-Assembled Nanoparticles of Testosterone-Modified Glycol Chitosan and Fructose Chitosan for Controlled Release - Quiñones, Javier Pérez; Gothelf, Kurt V.; Kjems, Jørgen; Heras, Angeles; Schmidt, Claudia; Peniche, Carlos (Journal of Biomaterials and Tissue Engineering)
Keywords: Biomedical Engineering; Medicine (miscellaneous); Bioengineering; Biotechnology

Embedding DNA in surfactant mesophases: The phase diagram of the ternary system dodecyltrimethylammonium–DNA/monoolein/water in comparison to the DNA-free analogue - Bilalov, Azat; Elsing, Jonas; Haas, Eva; Schmidt, Claudia; Olsson, Ulf (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Structural Evolution in the Isotropic Channel of a Water–Nonionic Surfactant System That Has a Disconnected Lamellar Phase: A 1H NMR Self-Diffusion Study - Stubenrauch, Cosima; Kleinschmidt, Felix; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

N,O6-partially acetylated chitosan nanoparticles hydrophobically-modified for controlled release of steroids and vitamin E - Quiñones, Javier Pérez; Gothelf, Kurt Vesterager; Kjems, Jørgen; Caballero, Ángeles María Heras; Schmidt, Claudia; Covas, Carlos Peniche (Carbohydrate Polymers)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry

Self-assembled nanoparticles of glycol chitosan – Ergocalciferol succinate conjugate, for controlled release - Quiñones, Javier Pérez; Gothelf, Kurt Vesterager; Kjems, Jørgen; Caballero, Ángeles María Heras; Schmidt, Claudia; Covas, Carlos Peniche (Carbohydrate Polymers)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry

Self-assembled nanoparticles of modified-chitosan conjugates for the sustained release of dl-α-tocopherol - Quiñones, Javier Pérez; Gothelf, Kurt Vesterager; Kjems, Jørgen; Yang, Chuanxu; Caballero, Angeles María Heras; Schmidt, Claudia; Covas, Carlos Peniche (Carbohydrate Polymers)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry

"Borussia", "Pfeffer", "Explosion" – Latinismen auf der Spur - Tophinke, Doris (Praxis Deutsch)

Streitgeschichten – ein Buchprojekt - Tophinke, Doris (Praxis Deutsch)

Andersschreiben als Gegenstand der linguistischen Forschung - Schuster, Britt-Marie; Tophinke, Doris (Andersschreiben. Formen, Funktionen, Traditionen)

Schreiben 2.0. Schriftlinguistische Beobachtungen und schriftdidaktische Perspektiven - Tophinke, Doris (Germanistische Mitteilungen. Zeitschrift für Deutsche Sprache, Literatur und Kultur)

Syntaktischer Ausbau im Mittelniederdeutschen. Theoretisch-methodische Überlegungen und kursorische Analysen - Tophinke, Doris (Niederdeutsches Wort)

Wild Style. Graffiti-Writing zwischen Schrift und Bild - Papenbrock, Martin; Tophinke, Doris (Andersschreiben. Formen, Funktionen, Traditionen)

“Seit ein Gespräch wir sind und hören voneinander” – eine Einführung - Rauh, B.; Laubenstein, Désirée; Anken, L.; Auer, H.-L. (Förderschwerpunkt Lernen – wohin?)

Für welches Ziel und zu welchem Zweck braucht man heute noch einen Förderschwerpunkt Lernen? - Rauh, B.; Laubenstein, Désirée; Auer, H.-L. (Förderschwerpunkt Lernen – wohin?)

Konstruktionen der Akteure im Förderschwerpunkt Lernen über Gegenwart und Zukunft ihres Gegenstandes – Ergebnisse der qualitativen Analyse von Expertendiskussionen. - Laubenstein, Désirée; Rauh, B. (Förderschwerpunkt Lernen – wohin?)